Legal nature of ECtHR practice - Kit, Taras (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The relevance of the topic is determined by the crucial role of the ECtHR practice in shaping the system of international human rights protection and ensuring fair justice. Of particular importance is the fact that the Court’s practice not only establishes the formal framework for the observance of substantive and procedural rights but also specifies their substantive and value-based content, forming standards that must be taken into account by national courts. In the context of harmonizing national legislation with European Union law and the existing challenges in implementing and interpreting the Court’s standards, a scholarly analysis of the legal nature of ECtHR practice is especially relevant for ensuring consistency in judicial practice and enhancing the effectiveness of human rights protection, which becomes even more significant in conditions of war and systemic human rights violations. The purpose of the study is to conduct a comprehensive analysis of the legal nature of the practice of the ECtHR. In particular, this research is focused on revealing the essence of ECtHR practice in its interconnection and through the three main legal functions of the Court’s activity - law enforcement, legal interpretation and supervisory control. To examine the legal nature of the ECtHR’s practice, such methods as the formal-logical, comparative-legal, dialectical, as well as analysis and synthesis, were employed. As a result of the conducted research, it has been substantiated that the status of ECtHR practice as a source of law arises precisely from the normative fixation of the rule that «courts are obliged to apply ECtHR practice as a source of law when considering cases». At the same time, this serves as a basis for its application in specific legal relations as an effective regulatory mechanism. It is argued that ECtHR practice is not a precedent in the sense of common law systems, rather, the so-called «precedent nature» of ECtHR practice, mentioned in the works of many scholars, should be understood in the context of maintaining the consistency of judicial practice. A conclusion has been drawn regarding the legal nature of ECtHR practice as a special type of judicial practice, characterized by a three-component structure, which includes: the law-enforcement component (where the ECtHR applies the provisions of the Convention to specific cases), the legal-interpretation component (where, in the process of resolving cases, the Court provides authoritative interpretation of the Convention and its Protocols) and the supervisory-control component (where the ECtHR exercises control over the compliance of states with their international obligations under the Convention, identifying structural and systemic violations).